Growth Inhibition of Colletotrichum gloeosporioides by Trichoderma harzianum, Trichoderma koningii, Bacillus subtilis and Pseudomonas fluorescens - Febrilia Nur ‘Aini; Sri Sukamto; Dwi Wahyuni; Risma Galuh Suhesti; Qurrotun Ayunin (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Colletotrichum  gloeosporioides is  a  disease  which  can  cause  significant yield  loss  of  cocoa.  The  objective  of  this  research  is  to  investigate  the  abilityof  antagonist  microbes,  Trichoderma  harzianum,  Trichoderma  koningii,  Bacillus subtilis  and Pseudomonas  fluorescens  in  controlling  gloeosporioides  biologically  in  laboratorium  condition.  The  experiment  was  carried  out  in  Crop  Protection  Laboratory,  Indonesian  Coffee  and  Cocoa  Research  Institute.  Results of  this  research  showed  that  antagonist  fungi,  T.  harzianum,  T.  koningii,  had  a stronger  ability  in  inhibiting  growth  of  C.  gloeosporioides about  83%  compared  to  the  ability  of  antagonist  bacteria,  B.  subtilis  and P.  fluorescens,  only about  49%. Key words: Growth  inhibition,  Colletotrichum  gloeosporioides,  Trichoderma  harzianum, Trichoderma koningii,  Bacillus subtilis, Pseudomonas fluorescens.